14+3x=(5x+4)-(2x+11)

Simple and best practice solution for 14+3x=(5x+4)-(2x+11) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 14+3x=(5x+4)-(2x+11) equation:


Simplifying
14 + 3x = (5x + 4) + -1(2x + 11)

Reorder the terms:
14 + 3x = (4 + 5x) + -1(2x + 11)

Remove parenthesis around (4 + 5x)
14 + 3x = 4 + 5x + -1(2x + 11)

Reorder the terms:
14 + 3x = 4 + 5x + -1(11 + 2x)
14 + 3x = 4 + 5x + (11 * -1 + 2x * -1)
14 + 3x = 4 + 5x + (-11 + -2x)

Reorder the terms:
14 + 3x = 4 + -11 + 5x + -2x

Combine like terms: 4 + -11 = -7
14 + 3x = -7 + 5x + -2x

Combine like terms: 5x + -2x = 3x
14 + 3x = -7 + 3x

Add '-3x' to each side of the equation.
14 + 3x + -3x = -7 + 3x + -3x

Combine like terms: 3x + -3x = 0
14 + 0 = -7 + 3x + -3x
14 = -7 + 3x + -3x

Combine like terms: 3x + -3x = 0
14 = -7 + 0
14 = -7

Solving
14 = -7

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| ln(4t+5)=4 | | 10y-3=2 | | 18u-5u+29=6u-27 | | -.06x=-1.8 | | 4m^2-16m+5=-2 | | A*A=1 | | 5(0)+4(-5)=-20 | | y-7.9=10 | | 5(0)+4y=-20 | | 17d+6=9d+38 | | 10p-2(3p-6)=4(3p+-6)-8p | | 4.6x+8-8.6x=4 | | 9(x-2)=-7.2 | | 10p-2(3p-6)=43p-60-8p | | 5(a+2)=7.2 | | 22,000-16,000/12×=1000 | | 29.2=4c-6 | | 7e-6=59.8 | | (x-2)(x+5)=18 | | 9x+14=2x+35 | | 2y+7=16-4y | | 9n^2+18n+14=6 | | 180-x-90-x=9x | | 9x+14=2x+25 | | 7p=25.2 | | 5x-28.4=x | | (1/3)3.14*5^2*6 | | 6(x-6.2)=4.2 | | (-3x-2)+(x-3)= | | 2z-3(x+6)=-4(x-1) | | (1/3)3.14*10*6 | | 17s+16=5s |

Equations solver categories